2017
DOI: 10.1016/j.otsr.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic fractures of the distal femur after total knee arthroplasty : Plate versus nail fixation

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…Our study was the rst investigation that ascertained the risk factors of PFF in the early postoperative period within 3 months. In univariate analysis, our signi cant factors, including age, RA, and neurologic disease, were similar to previous studies [3,5,6]. Although several pre-existing neurological diseases, including epilepsy, Parkinson's disease, and poliomyelitis were proposed as the risk factors [9], our study only had Parkinson patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our study was the rst investigation that ascertained the risk factors of PFF in the early postoperative period within 3 months. In univariate analysis, our signi cant factors, including age, RA, and neurologic disease, were similar to previous studies [3,5,6]. Although several pre-existing neurological diseases, including epilepsy, Parkinson's disease, and poliomyelitis were proposed as the risk factors [9], our study only had Parkinson patients.…”
Section: Discussionsupporting
confidence: 81%
“…Several risk factors have been recognized, which can be arranged into the patient, the surgical, and implant-related factors. Patient factors include advanced age, female gender, rheumatoid arthritis (RA), neurologic diseases, osteoporosis, and chronic steroid use [3,5,6]. While some surgical or technical errors such as anterior femoral notching (AFN) may increase the risk of PFF [1].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods of osteosynthesis have been proposed in surgical treatment strategies, such as single or double plating systems, intramedullary nailing (IM) and rTKA. However, recent reports emphasize that the final outcomes strongly depend on the fracture pattern and localization [ 6 , 8 , 24 ]. A study of periprosthetic tibial fractures found that Felix I fractures are associated with a higher risk of postoperative non-surgical complications, and that those treated with a proximal tibia replacement may cause the development of periprosthetic joint infections [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, every case should be particularly analyzed and the management matched individually. Several methods of treatment, including open reduction and internal fixation (ORIF) with plate and/or nail, and rTKA can be applied [ 7 , 8 , 9 ]. In some rare cases, in patients with loosened prosthesis, the fracture can occur at the level of the femur or the tibial shaft; it can also be found at the top of the prosthesis stem, where it is difficult and technically demanding to achieve stable fracture fixation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of patients seeking total knee arthroplasty on both sides is much more ambiguous. The new epidemiological reports estimate that up to 42% of people experiencing knee pain will require surgery on either knee [ 22 ]. Both techniques may be carried out at the same time or one at a time.…”
Section: Introductionmentioning
confidence: 99%